Exploring episodic specificity induction on divergent thinking in children - Guillermo Tomás; Teresa Bajo; Alejandra Marful (PLoS ONE, 2026)
Previous studies suggest that Episodic Specificity Induction (ESI) improves the recall of episodic details and facilitates transfer to other cognitive tasks requiring episodic thinking (i.e., divergent thinking). However, the only study examining an adapted future-oriented ESI in children has failed to show benefits in subsequent cognitive tasks. To investigate this, two experiments were conducted using the standard ESI protocol with children. Experiment 1 tested second graders, fifth graders, and young adults using children-adapted materials (i.e., TV cartoons), while Experiment 2 tested fifth graders using non-adapted materials. Both experiments confirmed that ESI improved the recall of episodic details compared to a control condition. Additionally, developmental differences in episodic recall in Experiment 1 disappeared after controlling for total verbal production, suggesting that children’s episodic memory benefits when recalling materials that are child-friendly. Conversely, unexpected findings regarding transfer effect to divergent thinking revealed no transfer effects in Experiment 2 (non-adapted materials) and a significant increase in idea fluency and flexibility following the control condition in Experiment 1 (children-adapted materials). This result may be explained by a positive mood induction, as general questions accompanied by child-friendly videos could enhance creative performance following the control condition. These findings highlight the importance of carefully selecting and adapting ESI materials to children population in future studies.